"A Gorgeous waste": solitude in Calvin and Hobbes. Issue 5 (2nd November 2019) - Abate, Michelle Ann
ABSTRACT: This essay examines the important but unexamined role that solitude plays in Calvin and Hobbes. The proclivity that Watterson's 6-year-old protagonist has for being by himself forms a core facet both to this specific character and to the comic as a whole. Many of Calvin's exciting adventures, along with an array of his most beloved qualities, have their origins in solitude. Whether he is frolicking in nature or fantasizing about travelling through outer space, the best times that Calvin experiences are routinely times that he spends alone. In so doing, this feature forms an overlooked aspect to the strip's premise as well as to its popularity. When the representation of solitude in Calvin and Hobbes is placed back within the comic's original historical context, it can be seen as offering a larger commentary about changes taking place in American daily life and especially within the realm of childhood in the closing decades of the twentieth century. During a time when the ability of individuals to spend time alone was increasingly scarce and even stigmatised, Calvin and Hobbes offered a powerful case study about the benefits, joys, and importance of solitude.